Development of Converter and Control System for Variable Speed Permanent Magnet Synchronous Generator in Small Hydro Power Plant Model - Thanajitr, Chatchaphong; Polmai, Sompob; Kittiratsatcha, Supat (My University, 2022)
In micro and small hydro power plants, the flow and head of the water fluctuate seasonally. The torque-speed characteristic of hydro turbine requires variable speed operation of generator to always obtain maximum power generation. This paper presents variable speed control of a permanent magnet synchronous generator and maximum power point tracking for small hydro power plant. The INC-like maximum power point tracking algorithm is proposed and implemented. The experimental results validate the proposed algorithm. However the speed fluctuations are observed and have to be addressed in future study.
Keywords: Micro Hydro Power Plant; MPPT; PMSG; Variable Speed